2015
DOI: 10.1177/1040638715608358
|View full text |Cite
|
Sign up to set email alerts
|

Sensitive detection of Porcine circovirus-2 by droplet digital polymerase chain reaction

Abstract: Abstract. Sensitive detection of Porcine circovirus-2 (PCV-2) is very important for surveillance of postweaning multisystemic wasting syndrome. Droplet digital polymerase chain reaction (ddPCR) is novel PCR method that can achieve high precision. Our study aimed to develop a sensitive assay utilizing ddPCR to detect PCV-2. Specificity of the assay was confirmed by the failure of amplification of DNA of other relevant viruses. The detection limit for ddPCR was 25 copies/μL, a 4-fold greater sensitivity than Taq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 16 publications
1
27
0
Order By: Relevance
“…Results are expressed as target copies per microliter of reaction [ 31 ]. In comparison with qPCR, the ddPCR technique has some favorable features, among which: 1) it performs absolute quantification based on the principles of sample partitioning and Poisson statistics, thus overcoming the normalization and calibrator issues [ 32 ]; 2) it has shown increased precision [ 33 ] and sensitivity in detecting low target copies [ 34 ]; 3) it is relatively insensitive to potential PCR inhibitors [ 35 37 ]; 4) it directly provides the result of the analysis expressed as number of copies of target per microliter of reaction (with confidence intervals) [ 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…Results are expressed as target copies per microliter of reaction [ 31 ]. In comparison with qPCR, the ddPCR technique has some favorable features, among which: 1) it performs absolute quantification based on the principles of sample partitioning and Poisson statistics, thus overcoming the normalization and calibrator issues [ 32 ]; 2) it has shown increased precision [ 33 ] and sensitivity in detecting low target copies [ 34 ]; 3) it is relatively insensitive to potential PCR inhibitors [ 35 37 ]; 4) it directly provides the result of the analysis expressed as number of copies of target per microliter of reaction (with confidence intervals) [ 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies on ddPCR show high sensitivity of the method and high precision for absolute quantification of DNA targets, for example in cancer [58], hepatitis B virus [9, 10], cytomegalovirus[11, 12], Chlamydia trachomatis [13, 14], Babesia microti , and Babesia duncani [15]. Comparison of ddPCR assays with real-time PCR assays showed that ddPCR assays had a higher sensitivity than real-time PCR assays [16, 17], but this was not confirmed in some other studies [11, 18]. Real-time PCR assays are widely used for detection and relative quantification of Plasmodium parasites.…”
Section: Introductionmentioning
confidence: 99%
“…In our present study, we used 3D digital PCR to accurately quantify the low levels of miRNA for validation in a large number of samples. Digital PCR, which is a third generation of PCR, has increased precision and sensitivity for detecting low amounts of target copies when compared to conventional quantitative real-time PCR (29,30). As such, it can be used for the detection and quantification of low levels of pathogens, rare genetic sequences, and cancer-related miRNAs (31)(32)(33).…”
Section: Discussionmentioning
confidence: 99%